Evaluación electrofisiológica del sistema auditivo y vestibular - Olmedo G., Diego; Chiti-Morales, Alessandra; Córdova J., Héctor; Delano, Paul H. (Revista Hospital Clínico Universidad de Chile, 2016)
The clinical evaluation of hearing loss in adult patients is usually performed by perceptualassessment through audiometer tests. This evaluation requires cooperation of the evaluatedsubjects. On the other hand, it is not possible to perform a perceptual audiometer test innewborns, and due to the need of an early audiological management of deafness in newborns-with hearing aids or cochlear implants-, modern medicine requires early diagnosis of hearingloss, preferably before the age of three months. Several electrophysiological clinical tools havebeen developed in audiology that allow us to make early diagnosis of hearing loss in thosewho are unable to respond an audiometry. The electrophysiological evaluation of the auditorysystem includes cochlear potentials, auditory brainstem responses, and cortical auditoryevoked potentials. On the other hand, the electrophysiological evaluation of the vestibularsystem includes the cervical and ocular myogenic vestibular potentials (cVEMPs and oVEMPs).This article also includes a brief description of otoacoustic emissions, which are not an electricmeasure of the central nervous system, but are widely used as a diagnostic tool in pediatricaudiology. The physiological advances in the knowledge of the auditory system allowed theearly diagnosis of hearing loss in the newborn. However, none of these electrophysiologicaltests replaces the perceptual evaluation of hearing thresholds with audiometric tests.